STUDI KOMPARATIF PENJUALAN TOMAT (Lycopersicum esculentum Mill.) LOKAL DAN NON LOKAL DI TINGKAT DISTRIBUTOR PASAR SEGIRI KOTA SAMARINDA - Widodo, Wahyu; Mariati, Rita (Jurnal Pertanian Khairun, 2023)
There are generally two types of tomatoes sold at Segiri Market, Samarinda City, namely local tomatoes and non-local tomatoes. The two types of tomatoes have many differences, including prices and stock in different markets. The purpose of this study was to determine the differences in prices and stocks of local and non-local tomatoes at the distributor level of Segiri Market, Samarinda City. This research was conducted for 12 weeks starting from September 2022 to November 2022. The data needed is primary data and secondary data with purposive sampling of 11 respondents, namely 4 respondents are local tomato distributors and 7 respondents are non-local tomato distributors. To find out the marketing channels for local tomatoes and non-local tomatoes at the Segiri Market distributor level, Sanarinda City, the snowball sampling method was used. Meanwhile, to find out the difference in price and stock of local and non-local tomatoes, an independent sample t-test can be used. The results of this study stated that the average price of local and non-local tomatoes had differences. Although based on the average price of local and non-local tomatoes had differences, when the sample t test was carried out for the selling prices of local and non-local tomatoes, it was known that the sig value. (2-tailed) of 0.193 0.05. So, according to the basis of decision making on the independent sample t test, it can be concluded that Ho is accepted and Ha is rejected. The sample t test for the purchase price of local and non-local tomatoes is known to have a sig value. (2-tailed) as much as 0.154 0.05. So, according to the basis of decision making in the independent sample t test, it can be concluded that Ho is accepted and Ha is rejected. Thus it can be determined based on the t test that there is no significant difference between the prices of local and non-local tomatoes. The amount of stock of local and non-local tomatoes also differs based on the average number of stocks. After testing the sample t test, it is known that the sig. (2-tailed) of 0.002 0.05. So, as the basis for decision making on the independent sample t test, it can be concluded that Ho is rejected and Ha is accepted. Thus it can be concluded that there is a significant difference between the number of local and non-local tomato stocks